PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PERAWAT PADA PUSKESMAS BAGUN PURBA KABUPATEN ROKAN HULU - ,Kurniawaty Fitri, Hani Fera , Zulfadil (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The purpose of this study was to determine the effect of work discipline and work motivation on nurse performance. This research took place at the Bangun Purba Health Center, Rokan Hulu Regency. In this study consists of four variables. These variables are Work Discipline (X1), Work Motivation (X2), Nurse Performance (Y). The data analysis method uses the Quantitative Descriptive method with the Multiple Regression analysis tool, with the help of using a statistical application, namely SPSS version 23. The results of the study show that: 1) Work Discipline has a significant effect on Nurse Performance. 2) Work motivation has a significant effect on nurse performance. 3) Work Discipline and Work Motivation together have a significant effect on Nurse Performance Keywords: Work Discipline, Work Motivation, Nurse Performance